Simultaneous laparoscopic nephroureterectomy and cystectomy: a preliminary report - Rodrigo Barros (International Brazilian Journal of Urology, 2008)
PURPOSE: Patients with muscle-invasive bladder cancer and concomitant upper urinary tract tumors may be candidates for simultaneous cystectomy and nephroureterectomy. Other clinical conditions such as dialysis-dependent end-stage renal disease and non-functioning kidney are also indications for simultaneous removal of the bladder and kidney. In the present study, we report our laparoscopic experience with simultaneous laparoscopic radical cystectomy (LRC) and nephroureterectomy. MATERIALS AND METHODS: Between August 2000 and June 2007, 8 patients underwent simultaneous laparoscopic radical nephroureterectomy (LNU) (unilateral-6, bilateral-2) and radical cystectomy at our institution. Demographic data, pathologic features, surgical technique and outcomes were retrospectively analyzed. RESULTS: The laparoscopic approach was technically successful in all 8 cases (7 males and 1 female) without the need for open conversion. Median total operative time, including LNU, LRC, pelvic lymphadenectomy and urinary diversion, was 9 hours (range 8-12). Median estimated blood loss and hospital stay were 755 mL (range 300-2000) and 7.5 days (range 4-90), respectively. There were no intraoperative complications but only 1 major and 2 minor postoperative complications. The overall and cancer specific survival rates were 37.5% and 87.5% respectively at a median follow-up of 9 months (range 1-45). CONCLUSIONS: Laparoscopic nephroureterectomy with concomitant cystectomy is technically feasible. Greater number of patients with a longer follow-up is required to confirm our results.